MANAJEMEN HUMAS BERBASIS E GOVERMENT DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK PENDIDIKAN ISLAM - Tri Yuli Lestari; Rahmat Hidayat; Romlah Romlah; Ali Abdul Wakhid (STKIP Pesisir Selatan, 2025)
Objective: This study aims to examine the role of e-government based public relations management in improving the quality of public services in Islamic educational institutions. The focus of the study is directed toward understanding the concept, strategic role, and implementation challenges of e-government based public relations management within the context of public services in Islamic education. The research method employed is a library research approach by reviewing various literature sources, including scholarly books, national and international journal articles, and policy documents relevant to public relations management, e-government, and public services in Islamic education. The data were analyzed using content analysis techniques through a descriptive analytical approach to identify patterns, concepts, and key findings from the reviewed literature. The results of the study indicate that e-government based public relations management plays an important role in enhancing the effectiveness, efficiency, transparency, and responsiveness of public services in Islamic education through the utilization of digital technology. The implementation of e-government is able to strengthen two way communication between Islamic educational institutions and the community, increase public trust, and build a professional and accountable institutional image.